PRAKTEK SIDANG CEPAT DI LUAR ATURAN HUKUM ACARA PERDATA DEMI EFISIENSI PENYELESAIAN PERKARA DI PENGADILAN AGAMA KOTA MALANG - zainul majdi; Khoirul Asfiyak; Moh. Muslim (JAS : Jurnal Ahwal Syakhshiyyah, 2020)
Background: the Religius courts of Malang city is a Judicial Instution that intended for Muslims in seeking justice because Malang Including areas with high cases than that was the background of rapid trial in addition it is also influenced by deficiencies related to limited courtroom and a small number of judges and in the trial practice there is something new, namely the trial process by examining two direct witnesses without being summoned one by one and related to the legal status of the decision in a speedy hearing, it is valid and legally binding. Methods: In this study using descriptive research with qualitative methods that are more inclined to the analysis. The data collection process was carried out in several ways, namely by Interviewing, Documentation and Observation with 4 research subjects. Results: The results of the study showed that there was a fast trial practice in the Malang Religious Court related to the background, practice and legal status of the verdict in the trial with the fast system. Conclusions: the conclusions include the reasons behind the quick trial, their practice and the legal status of the decisions in them.Keywords: Background, Practice, Legal Status of the Verdict in a quick trial